Cognitive performance is associated with cerebral oxygenation and peripheral oxygen saturation, but not plasma catecholamines, during graded normobaric hypoxia - Williams, T. B.; Corbett, J.; McMorris, T.; Young. J. S.; Dicks, M.; Ando, S.; Thelwell, R. C.; Tipton, M. J.; Costello, J. T. (Experimental Physiology, 2019)
We found that 1) performance of a complex central executive task (n-back) was reduced FiO2 0.12; 2) there was a strong correlation between performance of the n-back task and reductions in SpO2 and cerebral oxygenation; and 3) plasma adrenaline, noradrenaline, cortisol, and copeptin were not correlated with cognitive performance.